Organizational culture of the architectural firm: a case in a developing country. Issue 3 (2nd July 2016) - Lai, Kong Seng; Yusof, Nor'Aini; Kamal, Ernawati Mustafa
Abstract : The construction industry has been reported to experience problems in efforts to be innovative due to its complex nature. One of the factors that contributes to the problem is culture. Despite their perceived innovations, architectural firms have a limited understanding of their organizational culture in relation to innovation. This paper examines the organizational culture within the architectural firm in Malaysia, in response to the wider need for more organizational studies in the construction industry, especially in developing countries in Asia. A postal survey was employed and 151 architectural firms responded. The exploratory factor analysis revealed four cultural dimensions, namely (1) innovation-supportive behaviours, (2) freedom, (3) collectivism/teamwork and (4) individualism. The findings indicate that innovation-supportive behaviours and collectivism/teamwork were dominant in these architectural firms. The findings also revealed a lack of freedom and individualism within the architectural firms of Malaysia. Therefore future strategy should focus on encouraging more freedom and individualism within architectural firms as a way of fostering innovation, particularly in the context of developing countries.